1995
DOI: 10.1088/0953-8984/7/2/010
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic simulation studies of trapped hole bipolarons in BaTiO3

Abstract: Classical shell-model-and embedded-cluster-rype cdculuians are employed in order to supply thearetical arguments in favour of hale bipolarons in BaTiOx which have recently been speculated to exist in this photorefractive material. Our investigations concern the geometrical structure of hole bipolaram trapped at acceptor defects, their spin state and hole ionization energies. In particular the embedded-cluster modelling studies, which explicitly include the local electronic defect strncture. suggest the importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…We find that V Sr does not result in occupied gap states. However, our calculations show that O int 2--, a largely unexplored candidate defect [50], does. We previously found that O 2 is readily absorbed when epitaxial films of NdTiO 3 are exposed to air, and that it most likely resides in interstitial sites [51].…”
Section: Resultsmentioning
confidence: 61%
“…We find that V Sr does not result in occupied gap states. However, our calculations show that O int 2--, a largely unexplored candidate defect [50], does. We previously found that O 2 is readily absorbed when epitaxial films of NdTiO 3 are exposed to air, and that it most likely resides in interstitial sites [51].…”
Section: Resultsmentioning
confidence: 61%
“…(iii) Of great interest are detailed ab initio polaron simulations which would include the electron correlation effects (cf. [21]). This could give more confidence to the pre- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The modelling of the embedding lattice and of cluster-lattice interactions employs a shellmodel pair-potential description (see also references [18][19][20]). The shell-model parameters have been taken from the earlier work of Lewis and Catlow [2].…”
Section: Simulation Methodsmentioning
confidence: 99%